Co-delivery of proapoptotic peptide and p53 DNA by reduction-sensitive polypeptides for cancer therapy1. (21st May 2015) - Chen, Si; Rong, Lei; Jia, Hui-Zhen; Qin, Si-Yong; Zeng, Xuan; Zhuo, Ren-Xi; Zhang, Xian-Zheng
<x xml:space="preserve">Abstract</x> The xPolyR8–KLA(TPP)/p53 complex releases the p53 gene and C-KLA(TPP) in the cytoplasm, and initiates a more efficient cell apoptosis due to the regulation of both apoptotic pathways through p53 and C-KLA(TPP).